2017
DOI: 10.26443/el.v35i1-2.316
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Skills for Preservice Teachers: Do They Transfer to K-12 Classrooms?

Abstract: This study surveyed current education majors (n=70) in two Kansas universities to gain a perspective on their understanding of Information Literacy (IL) concepts and skills, and to learn whether they anticipated teaching such concepts to their future K-12 students. School media specialists in the state were also surveyed (n=85) and asked to share their observations of teachers new to the profession as to their understanding and practice of IL. Results indicate many education students were not familiar with IL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
4
17
0
2
Order By: Relevance
“…The findings of this study align with recent interviews of teaching staff in Alberta, Canada (another location with few school librarians), where teaching staff self-reported that they are unfamiliar with the term information literacy, and that a variety of competing priorities or time constraints affect how they approach imparting information literacy concepts (Smith, 2013). A lack of library collaboration, lack of familiarity with information literacy, and lack of time seem to be concerns with secondary school information literacy education that are consistent across recent related literature (Lee, Reed, & Laverty, 2012;Stockham & Collins, 2012;Togia, Korobili, Malliari, & Nitos, 2015).…”
Section: Commentarysupporting
confidence: 56%
“…The findings of this study align with recent interviews of teaching staff in Alberta, Canada (another location with few school librarians), where teaching staff self-reported that they are unfamiliar with the term information literacy, and that a variety of competing priorities or time constraints affect how they approach imparting information literacy concepts (Smith, 2013). A lack of library collaboration, lack of familiarity with information literacy, and lack of time seem to be concerns with secondary school information literacy education that are consistent across recent related literature (Lee, Reed, & Laverty, 2012;Stockham & Collins, 2012;Togia, Korobili, Malliari, & Nitos, 2015).…”
Section: Commentarysupporting
confidence: 56%
“…24 In a survey of education majors and school media specialists, Stockham and Collins found that many education students and recent graduates were unfamiliar with information literacy terminology and concepts. 25 To ameliorate this deficiency, teacher educators and librarians alike have encouraged collaboration between the two to effectively teach information literacy skills to students. 26 Nonetheless, a review of the literature reveals a lack of studies that provide a direct assessment of the information literacy skills among teacher education students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, it overlooks the context of the school as a workplace and there is a paucity of research into teachers' IL as a sociocultural practice. Symptomatic of this approach, the literature is primarily concerned with pre-service teachers' IL skills training (Fourie and Krauss, 2011;Johnson and O'English, 2003;Klebansky and Fraser, 2013;Stockham and Collins, 2012;Whitver, 2017), which necessitates a narrow focus on the university context and an over-reliance on the academic librarian as a panacea for teachers' IL development. For example, in their research on implementing IL instruction into teacher education programmes, Crouse and Kasbohm (2004) and Earp (2009) use the terms "information literacy training" and "library instruction" interchangeably and call for increased exposure of education students and teacher-educators to academic librarians in order to promote their IL skills.…”
Section: Introductionmentioning
confidence: 99%